Synthesis and characterization of thermo- and pH-responsive bacterial cellulose/acrylic acid hydrogels for drug delivery - Mohd Cairul Iqbal Mohd Amin; Naveed Ahmad; Nadia Halib; Ishak Ahmad (Elsevier, 2024)
Non-Indexed Publication